Meteorological data from ice-free areas on Soya Coast, East Antarctica ... - Kudoh, Sakae; Tanabe, Yukiko; Hayashi, Kentaro; Kida, Morimaru; Nobuhide, Fujitake; Uchida, Masaki; Imura, Satoshi (Arctic Data archive System (ADS), Japan, 2019)
Meteorological data recorded by automatic weather stations (AWSs) in the Yukidori Zawa (Yukidori Valley), Langhovde, and in Kizahashi Hama, Skarvsnes on the Soya Coast of East Antarctica ...